Perceptions of students on learning Arabic language vocabulary through a card game / Norshida Hashim... [et al.] - Hashim, Norshida; Syed Ahmad, Tuan Sarifah Aini; Mohd Ali, Siti Nur Dina; Abd Karim, Norfazlika (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Vocabulary is essential in mastering any languages. However, learning vocabulary is tedious as it requires students to memorize numerous words and perform a lot of exercises. Thus, it is essential to provide fun learning activities for learning vocabulary in order to promote students’ engagement in the learning process. Since the Arabic language is learnt in various levels of learning institutions such as schools and universities, a card game has a great potential to be utilized as a learning tool to enhance the learning of Arabic language vocabulary. This paper investigated perceptions of students on using a card game named as Ahsulu! in learning the Arabic language vocabulary at the intermediate level of Arabic language proficiency. This study involved students of Degree in Biology and Degree in Chemistry at Universiti Teknologi MARA Negeri Sembilan, Kuala Pilah Campus, Malaysia, who were selected based on purposive sampling. The data gathered by using an online survey and were analyzed descriptively by using Social Science Statistical Package (SPSS) Version 23. The findings suggest that using Ahsulu! as a learning tool could promote fun learning, ensure learning to take place and increase communication.